2020
DOI: 10.1021/acs.orglett.0c02091
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Catalyzed Reductive Aryl Thiocarbonylation of Alkene via Thioester Group Transfer Strategy

Abstract: Herein reported is a nickel-catalyzed reductive aryl thiocarbonylation of alkene via thioester group transfer strategy by using simple and readily available thioesters. In contrast to traditional activation of weaker C­(acyl)–S bond, the C­(acyl)–C bond of thioester was selectively cleaved to enable this reaction under mild conditions. Furthermore, this approach features operational simplicity and broad substrate scope, providing a complementary and practical route for thioester synthesis without requiring tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…These results indicated that insertion of Ni(I) into the S-S bond is easier and that the insertion of CO occurred after C-S or S-S bond cleavage. Based on the above the experimental data and previous work, 17 a plausible reaction mechanism is proposed in…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…These results indicated that insertion of Ni(I) into the S-S bond is easier and that the insertion of CO occurred after C-S or S-S bond cleavage. Based on the above the experimental data and previous work, 17 a plausible reaction mechanism is proposed in…”
Section: Resultsmentioning
confidence: 69%
“…Based on the above the experimental data and previous work, 17 a plausible reaction mechanism is proposed in Scheme 2. First, an Ni(0) species is formed by reduction with Zn powder, then, the species inserts into the Ph-I bond of the iodobenzene to form the intermediate A.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Purification by flash silica gel column chromatography (hexane/ethyl acetate = 10/1) afforded 2g (21.5 mg, 83%) as a colorless oil: Rf = 0.15 (hexane/ethyl acetate = 4/1). [3]…”
Section: S-(naphthalen-2-yl) 2-(13-dimethyl-2-oxoindolin-3-yl)ethanethioate (2g)mentioning
confidence: 99%
“…For example, the oxidative addition of compound I (Scheme 1a) to palladium affords a σ-aryl palladium intermediate, which is followed by alkene insertion to afford σ-alkyl palladium intermediate II because β-elimination does not occur owing to the formation of the adjacent all-carbon quaternary center; subsequent reaction with a nucleophile affords compound III. 1 Indeed, reactions of σ-alkyl palladium intermediate II with bis(pinacolate) diboron, 2 hexamethyldisilane, hexamethyldistannane, 3 and diethyl H-phosphonate 4 have been reported to afford the corresponding alkyl pinacol borane, silane, stannane, and phosphonate, respectively. Recently, we reported a palladium-catalyzed carbothiolation reaction affording IV using an alkyl and aryl TIPS thioethers, which proceeds via σ-alkyl palladium intermediate II generated from compound I (Scheme 1b).…”
mentioning
confidence: 99%